Mechanism of complement activation by radiographic contrast media. - Arroyave, C M (1977)
Activation of the complement system by radiographic contrast media (RCM) was demonstrated by in vitro haemolytic and immunological assays. Such activation was found to be a function of the RCM molar concentration. Iodipamide was the most active of five RCM tested. When RCM was incubated with normal human serum (NHS) in the presence of ethylene glycol-tetra-acetic acid and magnesium ions, conditions which block activation of the classical pathway but permit activation of the alternative pathway, haemolytically active C3, properdin and factor B were found to be decreased but haemolytically active C4 was normal. Using counterimmunoelectrophoresis, the activation of complement was further demonstrated by detection of C3 and factor B-split products. Finally, when radiolabelled complement proteins were reacted with RCM in vitro and studied by density-gradient ultracentrifugation, it was demonstrated that a large complex was formed with a sedimentation of 22S, similar in characteristics to the C5b-C9 complex. It was postulated that the mechanisms of in vitro consumption of complement by RCM was mainly through the alternative pathway.